AN EVALUATION ON TOEFL WORKSHOP PROGRAM USING STAKE'S COUNTENANCE MODEL - Yupika Maryansyah; Syukri Hamzah; Hadiwinarto Hadiwinarto (Universitas Muhammadiyah Makassar, 2023)
The Test of English as Foreign Language (TOEFL) is getting more and more important every day for both further study and career advancement. Accordingly, many educational institutions, both state-owned and private in Indonesia carry out innovative programs to increase their graduates' TOEFL scores. Universitas Muhammadiyah Bengkulu (UMB), as an educational institution is also carry out a program aiming to improve its graduates’ TOEFL score. The program is called as the TOEFL workshop for UMB students. This study is an evaluative study analyzing a program administered by UMB, TOEFL workshop for UMB students. The researchers used Stake Countenance Model as a method in the current study. The results of the study show that there is a contingency between antecedent, transaction, and outcome of the program of TOEFL workshop for UMB students.